Abdul Hamid Shilpakala Academy & Regional Cultural Center; A Cultural Center for The Haor Areas in Kishoregonj - Islam, Shanila (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2021.